PENGARUH PERSEPSI KUALITAS PRODUK TERHADAP NIAT PEMBELIAN ULANG PADA PRIVATE LABEL â€œCARREFOURâ€ DI CARREFOUR MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - HERAWATI, VINA (Universitas Katolik Widya Mandala Surabaya, 2012)
The purpose of this research is to know whether perceived product quality, customer satisfaction in categorical private label food products give significant influence both partially and totally toward repurchase intentions as mediating variable in Carrefour Surabaya. This research is dealing with the perceived product quality as the important factor in retailing, which consists of features, reliability, conformance, durability, serviceability, aesthetics, and perceived quality, and the effects toward repurchase intentions. This research is also dealing with , customer satisfaction, which is also an important factor in retail business and the effects toward repurchase intentions. The sampling technique used in this study is purposive sampling. Meanwhile, the analysis is using path analysis. Respondents were taken from all Carrefourâ€™s customers in the city of Surabaya. The results showed that there are significant between perceived product quality and customer satisfaction on repurchase intentions, and there is the influence of perceived product quality on customer satisfaction, and there is also significant of perceived product quality on customer satisfaction through repurchase intentions as a mediating variable.